Kepemimpinan Kiai dalam Membentuk Karakter Religius Santri di Pondok Pesantren Azzakariyah Kabupaten Merangin - Nurisa Nurisa; Rusmini Rusmini; Suci Fitriani (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2024)
The kiai as the leader of an Islamic boarding school has distinctive characteristics in shaping the religious character of students (santri). This study aims to examine the leadership of the kiai in shaping the religious character of students at Pondok Pesantren Azzakariyah, Muaro Panco Timur Village, Merangin Regency. The research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation. Data sources included the boarding school leader, teachers (ustadz/ustadzah), caregivers, and students. The findings reveal that: (1) Religious character development programs are implemented through daily activities such as congregational prayers, dhuha prayers, Qur’an recitation, muhadharah, and classical Islamic text (kitab kuning) studies; (2) The kiai’s leadership style is democratic and charismatic, reflected in his firmness and openness in decision-making, egalitarian social relations with teachers, and parental-like relationships with students; (3) Supporting factors in shaping students’ religious character include the role of teachers, organizational activities, family involvement, and the application of rewards and punishments, while inhibiting factors include students’ lack of self-awareness, family cultural influences, and students who are difficult to manage and tend to involve parents when sanctions are imposed.